A practical research on capillaries used as a front-end heat exchanger of seawater-source heat pump. (15th March 2019) - Liu, Long; Wang, Mingqing; Chen, Yu
Abstract: Traditional seawater-source heat pump (SWHP) needs to set water intake and titanium plate heat exchanger which result in high initial investment and large work quantity. A new type of SWHP was recommended, which use capillaries made by PPR (polypropylene random) submerged in seawater as the front-end heat exchanger. Glycol antifreeze solution was injected into the capillaries used as circulating medium. Capillaries were used as heat exchanger between seawater outside and glycol antifreeze solution inside. This method can greatly reduce the initial investment and improve COP of the SWHP system. This paper discusses the feasibility of capillaries used as the front-end heat exchanger of SWHP. An experimental platform was designed and constructed to measure the heat transfer coefficient of capillaries, and collect the operating data to calculate COP of SWHP in winter and summer. The experiment results show that, the average COP of the SWHP system is 3.17 in winter and 3.3 in summer. When the velocity of glycol in capillary tube is 0.15 m/s, the measured value of capillary heat transfer coefficient k is 161.01 W/(m 2 ·°C). The efficiency of capillary heat exchanger was greater than 96.4%, which shows that it is feasible to use capillaries as the front-end heat exchanger of SWHP. Highlights: A new type of seawater-source heat pump (SWHP) was recommended. Use capillary submerged in seawater as the front-end heat exchanger. The heat transfer coefficient of capillaries was measured. COP of SWHP system was calculated.